Trade, transportation and environment nexus in Nigeria - Longe, Adedayo Emmanuel; Ajulo, Kayode Daniel; Omitogun, Olawunmi; Adebayo, Emmanuel Olajide (The European Journal of Applied Economics, 2018)
This study investigates trade, transportation and environment nexus in Nigeria. The main objective of the study is to incorporate transportation activities and trade into the EKC model seeing transportation as an important factor that determines environmental degradation in Nigeria. Annual data from 1984 to 2014 is used in the study, whereas ARDL estimation technique was adopted to analyse the data. The results show that all the variables have a positive significant correlation with carbon emissions in Nigeria except trade that was negative and insignificant. According to ARDL estimates,trade, import transport services and GDP per capita have positive impact on CO2 emissions in the long-run while in the short-run, the result shows that trade, GDP per capita, energy consumption and transport services are capable of correcting about 74% deviation of carbon emissions back to long-run equilibrium. Based on the findings, drawn conclusion stipulates that energy consumption and trade are the main determinant factors that contribute to carbon emission and appropriate attention should be given to energy consumption by considering alternative efficient energy sources to curb the increasing emission in Nigeria.